2009
DOI: 10.1371/journal.pone.0006623
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Neuroanatomical Study of the Red Nucleus of the Cat, Macaque and Human

Abstract: BackgroundThe human red nucleus (Nr) is comparatively less well-studied than that of cats or monkeys. Given the functional importance of reticular and midbrain structures in control of movement and locomotion as well as from an evolutionary perspective, we investigated the nature and extent of any differences in Nr projections to the olivary complex in quadrupedal and bipedal species. Using neuroanatomical tract-tracing techniques we developed a “neural sheet” hypothesis allowing us to propose how rubro-olivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 58 publications
5
73
0
Order By: Relevance
“…We further demonstrated the possibility of the translocation of the position of the human NB from the ventral central gray to the dorsomedial part of the human pNr (Onodera and Hicks, 2009 [8]). The human ND is isolated in the ventral central gray and occupies the MTT as does the feline ND (in human: see especially Case 1 in Fig.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…We further demonstrated the possibility of the translocation of the position of the human NB from the ventral central gray to the dorsomedial part of the human pNr (Onodera and Hicks, 2009 [8]). The human ND is isolated in the ventral central gray and occupies the MTT as does the feline ND (in human: see especially Case 1 in Fig.…”
Section: Introductionmentioning
confidence: 77%
“…We offered the view that in humans, the nucleus accessorius medialis of Bechterew is not an integral part of the ventral central gray, like it is in the cat and monkey, but that it corresponds to the dorsomedial part of the Red nucleus (Onodera and Hicks, 2009 [8]). By this translocation of the human NB, fine myelinated fibers from the human NB occupy the medial part of the CTT (as demonstrated by the present DiI study) in contrast to the situation in felines, where the NB occupies an area within the MTT (Onodera, 1984 [7]).…”
Section: Discussionmentioning
confidence: 99%
“…Nigral and cerebellar projections have been shown to converge on neurons of the superior colliculus in the rat (Westby et al 1994). Similarly, these two structures seem to interact in the reticular formation (ShammahLagnado et al 1983(ShammahLagnado et al , 1987(ShammahLagnado et al , 1992Schneider et al 1985) and the nucleus of Darkschewitsch, which has been associated with the red nucleus based on its similar connectivity patterns (Onodera and Hicks 2009, 1998. The involved nuclei in the thalamus-that is, MDpl and CM/Pf-receive input from all structures mentioned here in the context of the assumed oculomotor network (Ono and Niimi 1986;Royce et al 1991;MacLeod and James 1984) and project to the frontal eye fields (Sadikot and Rymar 2009;Tanaka and Kunimatsu 2011).…”
Section: Network-specific Convergencesmentioning
confidence: 98%
“…Rutherford and colleagues (1984) noted that the inferior olive of the rat does not receive afferents from either the magnocellular or parvicellular parts of the red nucleus, regions as defined in the atlas of Paxinos and Watson (2014). This suggested that nomenclature used in different species does not reflect homologous structures Onodera and Hicks, 2009). The IODM receives input from the spinal trigeminal nucleus (Huerta et al, 1983;De Zeeuw et al, 1996).…”
Section: Afferents To the Principal Olivary Nucleusmentioning
confidence: 99%